Economic democracy index 1970-2016 - Cumbers, A, University of Glasgow (2019)
In the project we used secondary data used for the construction of the Economic Democracy Index. The sources were the Organisation for Economic Cooperation and Development (OECD), International Monetary Fund, World Bank, International Labour Organisation (ILOSTAT), and Institutional Characteristics of Trade Unions, Wage Setting, State Intervention and Social Pacts database (ICTWSS, Amsterdam Institute for Advanced Labour Studies), European Association of Cooperation Banks, European Values Study, World Values Survey, World Wealth and Income Database, and Worldwide Governance Indicators. In terms of geographical coverage, the dataset covers the OECD member countries and, depending on data availability, some indicators go back until 1970. The research project centres around the basic proposition that societies with strong and effective forms of economic democracy are more likely to achieve crucial public policy goals; such as combating climate change, reducing inequalities and creating more sustainable forms of economic activity. The research will construct an index of economic democracy (EDI) as a tool to test the basic proposition. As such, the research proposed fits directly within two of the ESRC's current priority areas of economic performance, and creating a vibrant and fair society. A key argument advanced here is that economic decision-making in many countries is becoming increasingly monopolised by a core of financial and political elites at the expense of the broader population. An increasingly narrow range of interests are therefore dominating economic decision making and policy failing to reflect the broad and diverse interest groups that constitute advanced capitalist societies. Not only is this leading to a democratic deficit in the management of society's resources and assets but it is argued that there are considerable negative public policy effects in terms of greater income and wealth inequalities, increasing susceptibility to financial crises and fragility, and arguably a failure to effectively ...